Low-grade epilepsy-associated neuroepithelial tumors: Tumor spectrum and diagnosis based on genetic alterations - Xie, Mingguo; Wang, Xiongfei; Duan, Zejun; Luan, Guoming (Frontiers in Neuroscience, 2023)
Brain tumors can always result in seizures when involving the cortical neurons or its circuits, and they were found to be one of the most common etiologies of intractable focal seizures. The low-grade epilepsy-associated neuroepithelial tumors (LEAT), as a special group of brain tumors associated with seizures, share common clinicopathological features, such as seizure onsets at a young age, predilection of involving temporal lobe, and almost benign course including a rather slow growth pattern and thus a long-term history of seizures. Ganglioglioma (GG) and dysembryoplastic neuroepithelial tumor (DNET) are the typical representatives of LEAT. Surgical treatments with complete resection of tumors and related epileptogenic zones are deemed the optimal way to achieve postoperative seizure control and lifetime recurrence-free survival in patients with LEAT. Although the term of LEAT was originally introduced since 2003, debates on tumor spectrum and diagnosis or classification of LEAT entities are still confusing among epileptologists and neuropathologists. In this review, we would further discuss these questions, especially based on the updated classification of central nervous system tumors in WHO 5th edition and the latest molecular genetic findings of tumor entities in LEAT entities.